Holy spirit movement in Korea: its historical and theological development. - Lee, Young-hoon (Fortress Press, 2009)
This book traces the historical and doctrinal development of the Holy Spirit Movement in Korea through five successive periods, from 1900 to the present. The first period (1900-20) was characterised by repentance and revival, the second period (1920-40) by persecution and suffering under Japanese occupation. The third period (1940-60) was a time of confusion and division, while the fourth period (1960-80) was a time of explosive revival in which the Pentecostal movement played a major role in the rapid growth of Korean churches. In the fifth period (1980 to the present), the Holy Spirit Movement reaches out to all denominations. The book also discusses the relationship between this movement and other religions, such as shamanism, and looks forward to further engagement with issues of concern in the larger society.